Correction: In search of autophagy biomarkers in breast cancer: Receptor status and drug agnostic transcriptional changes during autophagy flux in cell lines. - PLOS ONE Staff (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0262134.].